COVID-19-associated Multisystem Inflammatory Syndrome in Children Presenting as Acute Pancreatitis. Issue 5 (November 2020) - Stevens, James P.; Brownell, Jefferson N.; Freeman, A. Jay; Bashaw, Hillary
Abstract : ABSTRACT: In April 2020, a newly recognized pediatric disorder associated with COVID-19 characterized by significant inflammation with symptoms resembling Kawasaki disease was described by medical teams in the United States, the United Kingdom, and Italy. Before these reports, data from the initial COVID-19 outbreaks in China had not found the virus to cause significant morbidity or mortality in children. To date, pancreatitis has not yet been reported in either acute SARS-CoV-2 infection in children or the subsequent inflammatory syndrome. We describe a patient who presented with acute pancreatitis before rapidly progressing to multisystem organ dysfunction consistent with multisystem inflammatory syndrome in children due to COVID-19. Clinicians should be aware that in the context of the COVID-19 pandemic, pancreatitis can be an early presentation of multisystem inflammatory syndrome in children.